Analisa Efektifitas APE dalam Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Novany Putri, Finna Nanda; Parera, Siti Fatimah; Cici; Nailul Padhil Zohro; Sandra Aprilina (STAI Bumi Silampari, 2025)
Early Childhood Education (PAUD) is a crucial phase for child development, but in the field educators still often face the phenomenon of limited adaptive learning media to stimulate social-emotional aspects. This study aims to identify and evaluate the practice of making Educational Game Tools (APE) by educators and analyze their effectiveness on early childhood social-emotional development. The research method used is qualitative with a type of library research, where data is collected from various national and international academic journals in the last five years and analyzed using thematic analysis techniques. The results of the study show that innovative and contextual APE making practices by educators are able to significantly improve the ability to socialize, manage emotions, and form children's character. The use of media such as busy books and APE based on local culture has been proven to be effective in increasing children's enthusiasm, obedience to rules, and confidence in the learning environment. Thus, the creativity of educators in designing independent learning media is a determining factor in optimizing the achievement of children's social-emotional development in PAUD.